ANALISIS POLITIK TERHADAP USULAN PEMEKARAN DESA SIDARAJA KECAMATAN CIAWIGEBANG KABUPATEN KUNINGAN - Linggar Audia; Susilo Utomo; Fitriyah . (Journal of Politic and Government Studies, 2015)
This paper aims to describe how analysis political of the proposed expansion Sidaraja village, Subdistrict Ciawigebang, Kuningan District and factors - factors that affect the process of expansion Sidaraja Village area. This type of research used in this study is descriptive qualitative survey research base. Data collection techniques used observation, namely the collection of data by conducting direct observation of the object under study, where researchers conducted interviews directly with the informant questioning in connection with the problem under study and supported by secondary data. As for the population in this study is a component of the division Sidaraja village and community leaders in the village district Sidaraja Kuningan then the results of the data in a qualitative analysis.The results showed that there are three (3) process stage in the process of expansion Sidaraja Village, Ciawigebang SubDistrict, Kuningan District the first stage, the process whereby public aspirations sit together to deliberate for an agreement to split yourself. The second stage, the formation of the division committee after getting a deal to split themselves determine the division in charge of the committee to make a proposal to the regents proposed expansion. The third stage is the process of preparing draft. The factors - factors that affect the process of dividing the village Sidaraja Supporting Factors and factor inhibitors. Untill political dynamics in Sidaraja village expansion caused cancellation of Sidaraja expansion plans, Ciawigebang subdistrict, Kuningan district.